An exploratory study of the patients' sleep patterns and inflammatory response following cardiopulmonary bypass (CPB). Issue 15 (12th December 2013) - Casida, Jesus M; Davis, Jean E; Shpakoff, LaVonne; Yarandi, Hossein
<x xml:space="preserve">Abstract</x> Aims and Objectives To describe sleep patterns and inflammatory response postCPB, determine sleep pattern changes and inflammatory response over time and explore relationships between sleep and biomarkers of stress and inflammation. Background Despite the numerous citations of the role of sleep in restoration and health maintenance, a paucity of research exists about this phenomenon in patients undergoing CPB. Specifically, there is no research that has explored correlations between sleep patterns and systemic inflammatory response in adult cardiac surgery patients. Design Exploratory, repeated‐measures, correlational study. Method Subjects were recruited from a Midwestern urban hospital. Of the 25 eligible subjects, 16 males and four females completed the study. Wrist actigraphy was used to measure sleep variables. Salivary cortisol and C‐reactive protein (C‐RP) levels were measured daily. Data were collected during postoperative nights/days 1 through 4 (T1–T4). Results Subjects' sleep onset latency (SOL) median scores (0 minute) were within normal range across time periods, whereas median scores for wake after sleep onset (WASO > 270 minutes), sleep fragmentation index (SFI >51%), total sleep time (<153 minutes) and sleep efficiency index (SEI <36%) fell outside the normal ranges. Changes in the median sleep scores over time, however, were not significant at p > 0·05. Median cortisol levels were within normal range (0·3–0·8 μg/dl) from T1−T4, but the C‐RP level peaked at T2 (median = 2370 pg/ml). Strong correlations were found: (1) between SFI−cortisol (rs = 0·82), C‐RP (rs = 0·65) − WBC (rs = 0·69); (2) between SEI−C‐RP (rs = 0·58); (3) between WASO−WBC (rs = 0·48), WASO and cross‐clamp time (rs = 0·50); and (4) between SOL−age (rs = −0·55) at p < 0·05. Conclusions Subjects were severely sleep‐deprived with inflammatory response exaggerations warranting further investigations using larger sample sizes. Relevance to clinical practice This study offers a foundation for developing a conceptual model explaining mechanisms of sleep disturbance and inflammatory response postCPB. This knowledge is crucial for testing sleep‐promoting interventions to modulate inflammatory responses essential for preventing complications, and restoring health.